A Path toward Inherently Asymmetric Micromotors. (29th May 2022) - Chattopadhyay, Purnesh; Heckel, Sandra; Irigon Pereira, Fabio; Simmchen, Juliane
Abstract : Since the highly cited paper by Purcell postulating the "Scallop theorem" almost 50 years ago, asymmetry is an unavoidable part of micromotors. It is frequently induced by self‐shadowing or self‐masking, resulting in so‐called Janus colloids. This strategy works very reliably, but turns into a bottleneck once up‐scaling becomes important. Herein, existing alternatives are discussed and a novel synthetic pathway yielding active swimmers in a one‐pot synthesis is presented. To understand the resulting mobility from a single material, the geometric asymmetry is evaluated using a python based algorithm and this process is automated in an open access tool. Abstract : The as‐synthesized Pac‐Man TiO2 microparticles exhibit geometrical dissimilarity leading to nonuniform photochemical reaction on the surface of the photocatalyst followed by a directed motion. This can prove to be a scalable strategy in the development of an inherently asymmetric photocatalytic micromotor.